PENERAPAN GUIDED DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATERI PERPINDAHAN KALOR - Saly Windy Irene Alaria; Aswin Hermanus Mandolang; Patricia Mardiana Silangen (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2023)
This research aims to determine the improvement of student learning outcomes after participating in learning by using the guided discovery learning model on heat transfer material. The method used in the research is Classroom Action Research through two cycles, namely the first cycle of two meetings and the second cycle of one meeting. The subjects of this research were students of class XI MIA 1 SMA Negeri 1 Tabukan Utara totaling 20 students. The instruments used in this research are tests carried out at the end of each meeting and observation sheets. Of the 20 students with cognitive, affective, and psychomotor assessment results at the first meeting the percentage of completeness was 60% and increased at the second meeting to 80% while at the third meeting 95%.. This shows an improvement in student learning outcomes at the end of each lesson in cycles I and II. The results of this research show that learning by using guided discovery learning models can improve student learning outcomes on heat transfer material. Thus the application of guided discovery learning model can improve student learning outcomes on heat transfer material for students of class XI MIA 1 SMA Negeri 1 Tabukan Utara.